Efficacy and Safety of Sublingual Immunotherapy for Allergic Rhinitis in Pediatric Patients: A Meta-Analysis of Randomized Controlled Trials. Issue 1 (January 2017) - Feng, Bohai; Wu, Jueting; Chen, Bobei; Xiang, Haijie; Chen, Ruru; Li, Bangliang; Chen, Si
Background: Allergic rhinitis (AR) has become a global health problem that constantly affects a large part of the general population, especially children. Objective: Sublingual allergen immunotherapy (SLIT) has been used extensively for pediatric AR, although its efficacy and safety are often questioned. In this meta-analysis of randomized controlled trials (RCT), we evaluated the use of SLIT for pediatric AR. Methods: A number of medical literature data bases were searched through January 2016 to identify RCTs that examined the use of SLIT for pediatric AR and that assessed clinical outcomes related to efficacy. Descriptive and quantitative information was abstracted. Standardized mean differences (SMD) were calculated by using fixed- and random-effects models. Subgroup analyses were performed. Heterogeneity was assessed by using the I 2 metric. A network meta-analysis was used to estimate SMDs between two SLIT protocols for pediatric seasonal AR. All data were extracted from publications or received from the authors. Results: Twenty-six studies were eligible for inclusion in the meta-analysis of rhinitis or rhinoconjunctivitis symptom scores, and 19 studies were eligible for the meta-analysis of medication scores. Descriptive and quantitative data were extracted. SLIT differed significantly from placebo in terms of symptom scores (SMD -0.55 [95% confidence interval CI, -0.86 to -0.25]; p = 0.0003, I 2 = 90%) and medication scores (SMD -0.67 [95% CI, -0.96 to -0.38J; p < 0.00001, I 2 = 83%). Oral pruritus was the adverse effect, which occurred most commonly in children who were receiving SLIT. Network meta-analysis revealed no significant difference between the pre-coseasonal and continuous SLIT protocols for seasonal AR in symptom scores (SMD -6.55 [95% CI, -25.38 to 12.29]; p = 0.496) and medication scores (SMD -8.83 [95% CI, -22.10 to 4.43]; p = 0.192). Conclusions: Our meta-analysis results indicated that SLIT provided significant symptom relief and reduced the need for medication in pediatric patients Moreover, the safety of SLIT needs to be confirmed in RCTs with larger samples.